Alocação de Recursos em um fronthaul Óptico com functional split Recomendado para o 5G - Amaral, Murilo Porto (2020)
It is presented in this dissertation the application of functional split technic applied in an access network section model, tested on a dynamic optical fronthaul simulator developed fot the 5G technology. The adjustment made by selecting a level of the f